EKSISTENSI UNSUR MENS REA SEBAGAI SYARAT PEMIDANAAN DALAM PUTUSAN PENGADILAN - Puspita Lasambu; Hernawati RAS; Joko T Suroso (Program Studi Magister Ilmu Hukum Pascasarjana Universitas Langlangbuana, 2019)
The duty of a country of law is to carry out order and justice. The existence of the Indonesian Penal Code is an example of Indonesia's role as a state of law. One of the principles to impose criminal is the principle of error (Mens Rea). However, in the practice of court decisions, there are convictions in the absence of Mens Rea. Therefore, it needs to be investigated how the legal power of the conviction of where in its legal consideration states that there is no Mens Rea found? and how does the legal effort of convicted convicts that are already convicted while in their legal considerations, there's an absence of Mens Rea? This research uses a normative juridical approach, while the research specification is descriptive analytical. This research was conducted in two stages, through library research and field research, using qualitative methods as a method of data analysis and data collection techniques done by studying documents and the field.Based on the results of the study, it was found that in the Criminal Decision which in legal considerations there is no element of Mens Rea, is a decision that is legally flawed, therefore it can be terminated through legal effort. Penalty decisions that do not fulfill a sense of justice and already have permanent legal force, can be overturned through PK, and an effort of examination on the decision. However, the examination will not overturn the judge's decision.